PENGARUH ORIENTASI KEWIRAUSAHAAN, MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA BADAN USAHA MILIK DESA (BUMDes) DI KECAMATAN TAPUNG - Rahmani, Sofiah; Azlina, Nur; Nurulita, Suci (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to empirically analyze the influence of Entrepreneurial Orientation, WorkMotivation and Leadership on the Performance of Village-Owned Enterprises (BUMDes)in Tapung District. This study is a quantitative study. The population in this study wereVillage-Owned Enterprises (BUMDes) in Tapung District as many as 25 BUMDes. Thetotal number of respondents taken was 75 respondents. The sampling used in this studywas nonprobability sampling, namely saturated sampling. Data collection in this studyusing a questionnaire. The data analysis technique used in this study was multiple linearregression analysis. The analysis method in this study was carried out using the SPSS(Statistical Product and Service Solutions) version 30 program. The results of this studyindicate that Entrepreneurial Orientation affects the Performance of Village-OwnedEnterprises; Work Motivation affects the Performance of Village-Owned Enterprises andLeadership affects the Performance of Village-Owned Enterprises in Tapung District.Keywords: Entrepreneurial orientation, Work motivation, Leadership, performance ofvillage-owned enterprises.